MeONH2·HCl-Mediated α-Methylenation/Conjugate Addition of α-Sulfonyl o-Hydroxyacetophenones with Methyl Sulfoxides: Route to 3-Sulfonylchroman-4-ones - Chang, Meng-Yang; Chen, Kuan-Ting (Synthesis, 2021)
A novel and efficient route for the synthesis of 3-sulfonylchroman-4-ones from α-sulfonyl o-hydroxyacetophenones with methyl sulfoxides via a MeONH2·HCl-mediated sequential methylenation/ conjugate addition is described. Plausible reaction mechanisms are proposed and discussed. Various reaction conditions for this novel, one-pot, environmentally friendly conversion were investigated.
Keywords: chroman-4-ones; o-hydroxyacetophenones; methylenation; methyl sulfoxides; sulfonyl compounds